A collection of Islamic advertising principles: revisited and detailed. (2018) - Shafiq, Ali
This paper provides a detailed exposition of the principles of Islamic advertising, as found in the writings by religious and academic scholars and extracted from relevant verses of the Holy Qur'an . This paper is theoretical in nature and uses content analysis for the findings. The principles detailed here open newer and wider avenues for research in the area of Islamic marketing/advertising and will help in furthering the nascent concept of Islamic advertising. Islamic advertising concept stands contrary to the contemporary practices. As such this paper has great implications in terms of application of Islamic advertising to real-world practices too. With a growing concern for business ethics, the concept of Islamic advertising will not only eradicate the ill-effects of contemporary advertising, but will also provide sound evidence for revising advertising policies.